Perceptions of environmental change and use of traditional knowledge to plan riparian forest restoration with relocated communities in Alcantara, Eastern Amazon - Celentano, Danielle; Rousseau, Guillaume Xavier; Engel, Vera Lex [UNESP]; Facanha, Cristiane Lima; Oliveira, Elivaldo Moreira de; Moura, Emanoel Gomes de (Biomed Central Ltd., 2014)
Background: Riparian forests provide ecosystem services that are essential for human well-being. The Pepital River is the main water supply for Alcantara (Brazil) and its forests are disappearing. This is affecting water volume and distribution in the region. Promoting forest restoration is imperative. In deprived regions, restoration success depends on the integration of ecology, livelihoods and traditional knowledge (TEK). In this study, an interdisciplinary research framework is proposed to design riparian forest restoration strategies based on ecological data, TEK and social needs.Methods: This study takes place in a region presenting a complex history of human relocation and land tenure. Local populations from seven villages were surveyed to document livelihood (including 'free-listing' of agricultural crops and homegarden tree species). Additionally, their perceptions toward environmental changes were explored through semi-structured interviews (n = 79). Ethnobotanical information on forest species and their uses were assessed by local-specialists (n = 19). Remnants of conserved forests were surveyed to access ecological information on tree species (three plots of 1,000 m(2)).Results included descriptive statistics, frequency and Smith's index of salience of the free-list results. Results: The local population depends primarily on slash-and-burn subsistence agriculture to meet their needs. Interviewees showed a strong empirical knowledge about the environmental problems of the river, and of their causes, consequences and potential solutions. Twenty-four tree species (dbh > 10 cm) were found at the reference sites. Tree density averaged 510 individuals per hectare (stdv = 91.6); and 12 species were considered the most abundant (density > 10ind/ha). There was a strong consensus among plant-specialists about the most important trees. The species lists from reference sites and plant-specialists presented an important convergence.Conclusions: Slash-and-burn agriculture is the main source of livelihood but also the main driver of forest degradation. Effective restoration approaches must transform problems into solutions by empowering local people. Successional agroforestry combining annual crops and trees may be a suitable transitional phase for restoration. The model must be designed collectively and include species of ecological, cultural, and socioeconomic value. In deprived communities of the Amazon, forest restoration must be a process that combines environmental and social gains.